Tingkat Pengangguran Akibat Covid-19 di Provinsi Nusa Tenggara Barat - Ikang Murapi; Dewa Ayu Oki Astarini; I Nyoman Subudiartha (Riset, Ekonomi, Akuntansi dan Perpajakan (Rekan), 2021)
This study aims to determine the increase in the unemployment rate due to Covid 19 in West Nusa Tenggara Province. This type of research is a descriptive method using secondary data which is analyzed using growth analysis at the unemployment rate. The results showed that of the 3.82 million working age population, there were 455.56 thousand people (11.93 percent) who were affected by Covid-19. Most of the working age population affected by Covid-19 experienced a reduction in working hours, namely 378.85 thousand people (83.16 percent). Meanwhile, the number of unemployed due to the impact of Covid-19 was 28.39 thousand people or around 25.03 percent of the total unemployed (113.43 thousand people) in NTB. The results of these calculations are carried out qualitatively by referring to tables and graphs during the period 2018-2020